REWETTING DESIGN FOR TROPICAL PEATLAND RESTORATION - Ainun Hasanah; Muhammad Farouk Setiawan (Sociae Polites, 2020)
Peatlands located in tropical climates are estimated to have an area of ​​11% of the total peatland on earth. The scope of ​​tropical peatland is proportional to the significant role this ecosystem plays in the stability of the earth and everything in it. Various efforts have been made to restore the condition of the peatland ecosystem, especially in tropical areas that have been affected by human activities. This study using the literature review method attempts to collect and summarize various peatland restoration efforts carried out in various countries in the world, then serve as a reference and basis for consideration in redesigning peat rewetting infrastructure. The result of this study is a canal blocking design using a PVC pipe filled with peat soil in its cavity. The layout of this PVC pipe canal blocking is designed by considering various factors. Challenges and prospects related to the idea of ​​this canal blocking with PVC pipe were also taken into consideration in the design. It is hoped that the innovation of canal blocking materials can increase resource efficiency and fund for canal blocking construction while maintaining its function and development objectives. Keywords: peatland rewetting design, canal blocking, PVC pipe